Comparison of Zinc-Probiotic Combination Therapy to Probiotic Therapy Alone in Treating Acute Diarrhea in Children - Zakaullah Kakar, Abdul Baqi Essazai, Syed Moeed Ahmed, Naseeb Ullah, Pir Jan, Najeebullah, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the efficacy of zinc-probiotic combination therapy and probiotic therapy alone in the treatment of acute pediatric watery diarrhea. Study Design: Randomized Clinical Controlled trial. Setting: The study was completed at The Department of Pediatrics, Unit I, Bolan Medical Complex Hospital, Quetta, Pakistan from July 2021 to January 2022. Methodology: A total number of 144 children of either gender aged 3 months to 5 years presented with acute watery diarrhea were included. Patients were randomly allocated into either Group-A (zinc supplementation with probiotics) or Group-B (only probiotics) for the treatment of acute diarrhea. Relief from diarrhea and duration of diarrhea were the main study end-points. Results: In a total of 144 children, the mean age was 27.04+14.43 months while the mean duration of diarrhea was 8.05+5.18 hours. On comparison of recovery from diarrhea, all the 72 children who received combination of probiotics and zinc were recovered from diarrhea, while 4 children (5.6%) children did not recovered from diarrhea within 5 days after starting the treatment in probiotics alone group (p=0.04). Duration of diarrhea was 27.63±14.22 hours in probiotics plus zinc group and 38.86±20.70 hours in probiotics only group (p<0.001). Practical Implications: Combination of probiotics with zinc resulted in early recovery among children with acute diarrhea but further randomized controlled trial enrolling large sample size from local population are necessary to verify the findings of this study. Conclusion: Combination of probiotics and zinc was superior as compared to the probiotics alone in the treatment of acute diarrhea in children. Keywords: Diarrhea, probiotics, recovery, stool, treatment, zinc.